APLIKASI ABDHI BERBASIS ANDROID SEBAGAI MEDIA PENDIDIKAN KESEHATAN GIGI DI MASA PENDEMI COVID-19 - Pawarti Pawarti; Fathiah Fathiah; Yeni Maryani; Jojok Susatyo (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
Dental caries is still a priority for children's health problems, the prevalence of dental caries in children aged 3-4 years in West Kalimantan is 49.83% in 2018. Dental caries in children who are not treated can cause chewing disorders which result in growth disorders. Lack of maternal knowledge about how to care for teeth is one of the causes of dental caries in children. Mother's knowledge about how to care for teeth can be obtained from counseling and communication media. The development of communication media tools such as cellphones, smartphones, and iPhones makes it easier for people to access information including information about health. During the Covid-19 pandemic, face-to-face counseling activities were not possible due to health protocols, therefore counseling using applications is a solution in conveying messages to the public, especially about how to care for children's teeth. The purpose of this study was to examine the effect of android-based counseling called the ABDI application on maternal knowledge in caring for children's teeth.This type of research is a quasi-experimental study with a pretest and postest control design. The population in this study were pregnant women and mothers under five at the Puskesmas UPTD West Pontianak. As samples were 76 pregnant women and mothers under five who visited the Puskesmas UPTD West Pontianak in June 2020. Data analysis used T-test to determine differences in maternal knowledge before and after using the ABDHI application.The results of the univariate analysis showed that there was an increase in the knowledge score of 14.5 after counseling using the ABDHI application, this increase was greater than the control group of 8.7. Bivariate analysis showed that there was a significant difference in knowledge before and after counseling using the ABDHI application with a value of p = 0.00 and there was a difference in knowledge between the experimental group and the control group with a value of p = 0.001. Keywords: ABDHI application, Mother's knowledge